The Use of Google Classroom As A Blended Learning Method For Eighth Grade English Learners SMP Muhammadiyah Rappang - Abd Kahar; Syahrir L; Usman M; Syamsunir Syamsunir (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
In this study, Google Classroom's use as a web-based teaching tool for 8th-grade English courses at SMP Negeri Muhammadiyah Rappang is investigated. The research employed a qualitative descriptive approach to examine Google Classroom-related problems faced by teachers and students. In-depth interviews, questionnaires, and unbiased observation were used to gather the data. The outcomes demonstrated that students had favorable perceptions of utilizing Google Classroom. The study's first dimension was on how simple it was to utilize, download lessons, and send assignments. The majority of respondents—about 68%—agreed that Google Classroom improved learning productivity for eighth-graders. The effectiveness of Google Classroom was the second factor, and 44% of respondents concurred that it was simple to use. The third dimension addressed Google Classroom usage challenges such as slow internet connections, media availability limitations, and student aptitudes. Concerning network connection restrictions, 24 respondents (47.1%) agreed while 29.4% disagreed. The fourth dimension concentrated on internet quota and network-related solutions. The majority of respondents concurred that developing new networks, asking for support from the school or parents, or all three might aid in overcoming these obstacles